AUDITORÍA DE GESTIÓN AL GAD PARROQUIAL DE SANTIAGO DE LA PROVINCIA DE LOJA, PERIODO 1 DE ENERO AL 31 DE DICIEMBRE DEL 2015 - Ramón Torres, Richard Nixon (2018)
The Management Audit is a valuable tool for the public sector, aims to advise and recommend corrective actions that prioritize the use of resources and allow better range of results in management and achievement of the raised corporate objectives, so that the present work research has the general objective: "Performing an Audit Management GAD SANTIAGO PARISH IN the PROVINCE of LOJA, PERIOD 1 JANUARY to 31 DECEMBER 2015" for it considering the following specific objectives Check in the state the degree of compliance with institutional objectives and goals some management audit procedures were performed; the autonomous government decentralized Santiago has not been audited in previous periods were included in this audit process: internal controls was conducted and completed by applying a questionnaire addressed to officials of the institution, which allowed us to evaluate the system administrative and financial likewise the achievement of objectives and goals which owns PARISH SANTIAGO GAD and thus meet some shortcomings that owns the entity's internal control. To evaluate the internal control system are defined and selected indicators; efficiency, effectiveness and economy, adequate to allow us to 5 quantify and subsequently estimate, to show what were the effects of actions taken last time regarding the different areas covered by this audit process. The idea is that these indicators affirm the groundwork to finalize and to instruct actions to take in the present and in the future. Finally, a report addressed to the president of GAD PARISH SANTIAGO containing the documentation generated throughout the audit process management as well as the respective conclusions of the analysis of the results of having applied management indicators and the findings will be delivered to were found; as recommendations which will be presented in suitable and successful solution or improvement in the future for the institution that requires change for alternatives.